Influence of Work Quality and Work Performance on Career Development of Employees of Dukcapil City of Medan - Bangun, Rosniwaty Br.; Hasanah, Uswatun; Waruwu, Khamo; Sari, Ira Manda (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
One of the most important elements in realizing good governance for the implementation of staffing management is the career development of employees. This research aims to find out the influence of work quality and work performance on the career development of employees of the Medan City Dukcapil Office. The research method used is quantitative with the t-test hypothesis. The results showed that there was a significant influence simultaneously and partially between the quality of work and work performance on the career development of employees of the Medan City Dukcapil Office. This is because employee career development programs can increase self-confidence and motivate employees in producing good job performance and have an impact on increasing the credibility of the company. The quality of work will encourage career development if all aspects that support the quality of work are met.